Penerapan Metode Demonstrasi Untuk Meningkatkan Hasil Belajar Ipa Pada Siswa Kelas 5A SDI Bhoanawa 1 - Maria Gorety Lami (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This study aims to improve science learning outcomes through demonstration methods in grade 5A SDI Bhoanawa 1. This type of research is a Classroom Action Research (CAR) which is carried out in two cycles. The subjects of this study were 20 students consisting of 14 boys and 6 girls in grade 5A SDI Bhoanawa 1. The research data were collected through observation, test and documentation methods. The research data were analyzed using simple descriptive statistical analysis methods. The results showed an increase in learning outcomes from pre-action by 5%, to 45% in cycle 1 and a maximum increase of 100% in cycle 2. So it can be concluded that applying the demonstration method can improve science learning outcomes in grade 5A SDI Bhoanawa 1 students.